Direct Synthesis of Co-doped Graphene on Dielectric Substrates Using Solid Carbon Sources - Wang, Qi; Zhang, Pingping; Zhuo, Qiqi; Lv, Xiaoxin; Wang, Jiwei; Sun, Xuhui (Nano-Micro Letters, 2015)
Direct synthesis of high-quality doped graphene on dielectric substrates without transfer is highly desired for simplified device processing in electronic applications. However, graphene synthesis directly on substrates suitable for device applications, though highly demanded, remains unattainable and challenging. Here, a simple and transfer-free synthesis of high-quality doped graphene on the dielectric substrate has been developed using a thin Cu layer as the top catalyst and polycyclic aromatic hydrocarbons as both carbon precursors and doping sources. N-doped and N, F-co-doped graphene have been achieved using TPB and F16CuPc as solid carbon sources, respectively. The growth conditions were systematically optimized and the as-grown doped graphene were well characterized. The growth strategy provides a controllable transfer-free route for high-quality doped graphene synthesis, which will facilitate the practical applications of graphene.